Android Battle Game Based on Augmented Reality with 2D Object Marker - Muhammad Fauzan Azim; Eka Wahyu Hidayat; Andi Nur Rachman (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2018)
This research develops the game by applying the Augmented Reality (AR) system in making games. Similar games that have been observed have a weakness where the Augmented Reality characters that appear do not match the marker, there is no calculation of the distance between the marker card as a battle trigger, and no character has raised the urband legend. For this reason, it is necessary to make a similar game by applying the Based Tracking Marker technique by calculating the distance of action between two markers by raising the theme of urband legend Indonesia and foreign legend legend. This research succeeded in making Multimedia battle fighting game products using the Multimedia Development Life Cycle (MDLC) method approach - Luther. Based on the tests that have been carried out, the alpha test results are functionally appropriate and from the beta testing the results of the User Acceptence Test (UAT) functionalities obtained a value of 71% declared feasible to use with the interpretation of